On the robustness of marginal abatement cost curves: the influence of world energy prices - Gernot Klepper; Sonja Peterson (Kiel Institute for World Economics (IfW), 2003)
Since the study of Ellerman and Decaux (1998) marginal abatement cost curves (MACCs) have become one of the favorite instruments to analyze the impacts of the implementation of the Kyoto Protocol and emission trading. This paper shows that the MACC in one country depends - via the link of world energy prices - on the level of abate-ment in the rest of the world. The strength of the dependence is influenced by factors, such as trade elasticities and trade structures. After discussing the mechanism theoretically, the CGE model DART is used to quantify the effects. We show that the MACC of a region does indeed shift with changes in the abatement level in the rest of the world and that especially with low domestic abatement level the MACCs can differ considerably.
Keywords: C68; D58; F18; Q41; 330; energy prices; computable general equilibrium model; DART; marginal abatement costs; Klimaschutz; Emissionsrechte; Kostenfunktion; Energie; Preis; Rohstoffpreis; Internationale Wirtschaftsbeziehungen; Allgemeines Gleichgewicht; Theorie; Welt